2017 IEEE Information Theory Workshop (ITW) 2017
DOI: 10.1109/itw.2017.8277946
|View full text |Cite
|
Sign up to set email alerts
|

On the capacity of index coding problems with symmetric neighboring interference

Abstract: A single unicast index coding problem (SUICP) with symmetric neighboring interference (SNI) has equal number of K messages and K receivers, the kth receiver R k wanting the kth message x k and having the side-information. , x k+D } is the interference with D messages after and U messages before its desired message. Maleki, Cadambe and Jafar obtained the capacity of this symmetric neighboring interference single unicast index coding problem (SNI-SUICP) with (K) tending to infinity and Blasiak, Kleinberg and Lub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…In this section, we give scalar linear index codes for SUICP(SNI) with arbitrary K, D and U . In [13], we proved Lemma 1 by proving the capacity of SUICP(SNI) with arbitrary K, D and U = gcd(K, D + 1) − 1. This lemma is useful to derive Theorem 2 of this section.…”
Section: Scalar Linear Index Codes For Suicp(sni)mentioning
confidence: 95%
See 1 more Smart Citation
“…In this section, we give scalar linear index codes for SUICP(SNI) with arbitrary K, D and U . In [13], we proved Lemma 1 by proving the capacity of SUICP(SNI) with arbitrary K, D and U = gcd(K, D + 1) − 1. This lemma is useful to derive Theorem 2 of this section.…”
Section: Scalar Linear Index Codes For Suicp(sni)mentioning
confidence: 95%
“…Proof. Let a and b be the non negative integers satisfying (13). Consider an SUICP(SNI) with K + a messages [x 0 x 1 .…”
Section: Scalar Linear Index Codes For Suicp(sni)mentioning
confidence: 99%
“…In [18], we showed that the capacity of SUICP-SNI for arbitrary K and D with U = gcd(K, D + 1) − 1 is…”
Section: A Single Unicast Index Coding Problem With Symmetric Neighbmentioning
confidence: 99%
“…In our problem, the total number of subfiles that the server needs to send can be exponential in the number K of users and further, the size of subfiles can be distinct in general. Therefore, existing algorithms [17]- [19] for the conventional index coding problem and the recent algorithms for the index coding problems with interlinked cycles [20] and symmetric neighboring interference [21] are not appropriate for our setting.…”
Section: Introductionmentioning
confidence: 99%